2016
DOI: 10.11607/jomi.4048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Different Crown Heights and Two Different Bone Types on Implants Placed in the Posterior Maxilla: Three-Dimensional Finite Element Analysis

Abstract: The purpose of this study was to determine the amount and localization of functional stresses in implants placed in two different bone types (type 3 and type 4) with three different crown heights in the atrophic posterior maxilla using finite element analysis. Materials and Methods: A three-dimensional finite element model of the posterior maxilla was created from a computerized tomography image by using the Marc 2005 (MSC Software) program. Three different crown/implant ratios (1/1, 1.5/1, 2/1) in the first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In contrast, when the cantilever was not used, the MBL is independent from the C / I ratio [ 28 ]. Using the finite element method, it was demonstrated that the stress concentration and stress distribution increase with the height of the crown [ 29 , 30 ]. As the C / I ratio increased twice, the von Mises stresses rose by about 47%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when the cantilever was not used, the MBL is independent from the C / I ratio [ 28 ]. Using the finite element method, it was demonstrated that the stress concentration and stress distribution increase with the height of the crown [ 29 , 30 ]. As the C / I ratio increased twice, the von Mises stresses rose by about 47%.…”
Section: Discussionmentioning
confidence: 99%
“…As the C / I ratio increased twice, the von Mises stresses rose by about 47%. At the C / I ratio of 2/1, the highest stresses were observed around the implant neck [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, published data on stress patterns around implants of different lengths on surrounding bone are few. Whenever an implant is loaded, the load is transferred to the abutment, which carries it to the fixture and through the implant abutment and implant bone connection to the surrounding peri-implant bone [3]. Therefore, in the present study we aim to examine the role of implant height on stress and strain distribution patterns within the implant system and surrounding peri-implant bone.…”
Section: According To Classification System Proposed Bymentioning
confidence: 99%
“…Clinically, low-density bone is associated with reduced implant survival rates compared to those bone of normal-density [8]. With other biomechanical studies having found no correlation between bone density and stress distribution, however, consensus remains unresolved [3,9].…”
Section: Introductionmentioning
confidence: 99%